Gender Anthropology of Prehistoric Populations: The Case of "Improperly" Oriented Graves at the Mokrin Necropolis - Marko Porčić (Etnoantropološki Problemi, 2010)
This paper explores some gender anthropology issues in a prehistoric context. Specifically, the paper attempts to shed light on the question of why certain male and female persons were interred in positions contrary to the strict norm that applied to the burial of men and women at the early Bronze Age necropolis in the town of Mokrin near Kikinda. Three elements have been analyzed, namely physical activities, funerary offerings, and the layout of the necropolis. The analysis points to the conclusion that in the early Bronze Age society of Mokrin inverted gender identities were to be found.